LIVELIHOOD ENHANCEMENT OF FISHERMEN COMMUNITY : A CASE STUDY IN GANDHISAGAR RESERVOIR, MADHYA PRADESH - SUBUDDHI, U K; CHOUDHARY, R K; DAS, A K; BALAPURE, SATISH (Journal of the Inland Fisheries Society of India, 2020)
Socio-economic conditions and livelihood status of the fishing community of Gandhisagar reservoir in Mandsaur district was studied to assess the impact of the beneficial schemes run by Fisheries Federation of Madhya Pradesh. Data were collected from randomly selected 50 fishermen through participatory rural appraisal and personal interview using a well structured questionnaire. The preliminary results were validated through Focus Group Discussions. The result showed that the schemes have positive impact on the fisherfolk as the migration of the fishermen to any other occupation got decreased. They are now quite sufficient to acquire the materials, which are needed for fishing activity, on day to day basis. Key words: Gandhisagar reservoir, fishers community, socio-economic, Madhya Pradesh Fisheries Federation, Livelihood